The Effect of User Psychology on the Content of Social Media Posts: Originality and Transitions Matter - Chen, Lucia Lushi; Magdy, Walid; Wolters, Maria K. (Frontiers in Psychology, 2020)
Multiple studies suggest that the frequencies of affective words expressed on social media text is associated with the user's personality and mental health status. In this study, we re-examine these associations by looking at the transition patterns of affect. We analyzed 4086 posts from 70 adult Facebook users contributed over two months, including its content and affect polarity. We studied posting behaviour including the silence periods the user does not post any content. We also flagged posts that were identified as lyrics or quotes. Our results show that more agreeable participants tend to post positive content continuously, and participants on the high end of neuroticism are characterized by rapid changes between posting positive and negative content. We also observe that participants with stronger depression symptoms posted more non-original content. Our study inspired future approaches to incorporate the transitions of affective pattern derived from social media text and their content originality as predictive variables in automatic detection of wellbeing/mental disorder symptom.